Carbon dioxide chemical chain cracking coupling catalytic disproportionation immobilization method

By using the perovskite catalyst La2NiFeO6 in the CO2 chemical chain cracking and coupling catalytic disproportionation reaction, the problems of insufficient catalyst stability and low carbon sequestration efficiency were solved, and efficient and stable CO2 fixation and CO yield improvement were achieved.

CN119430180APending Publication Date: 2025-02-14CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411634306.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing carbon dioxide fixation technology, there are problems of insufficient catalyst stability and low carbon sequestration efficiency.

Method used

The perovskite catalyst La2NiFeO6 is used as the oxygen carrier, and the catalytic disproportionation reaction is coordinated through the cracking of CO2 chemical chains, and the coordinated catalytic action of Ni and Fe and the regulation of oxygen vacancies are used to achieve efficient and stable CO2 fixation.

Benefits of technology

It improves CO2 fixation efficiency, improves CO yield and carbon sequestration rate, and the catalyst has better circulation performance and stability, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430180A_ABST
    Figure CN119430180A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon dioxide chemical-looping cracking coupling catalytic disproportionation immobilization method, which uses a perovskite catalyst to realize CO2 chemical-looping cracking through redox cycle. The obtained CO enters a disproportionation reactor to be subjected to disproportionation reaction under Fe-based catalysis to generate C and CO2, the CO2 and the CO which does not participate in the reaction are separated through a separation membrane technology, and the CO2 and the CO enter a cracking reactor and the disproportionation reactor respectively to be recycled, so that the C fixation rate is expected to be maximized. The process consists of a cracking reactor, a regeneration reactor and a disproportionation reactor. According to the carbon dioxide chemical chain cracking coupling catalytic disproportionation immobilization method, through continuous conversion of the oxygen carrier # imgabs0 # and efficient cracking of CO2, coupling of CO catalytic disproportionation and addition of the separation membrane, the C immobilization rate can be obviously increased, carbon dioxide emission reduction and recycling of low-quality fuel gas are achieved, and the carbon dioxide chemical chain cracking coupling catalytic disproportionation immobilization method is suitable for industrial production. By adjusting the specific composition and structure of the catalytic oxygen carrier and the surface morphology of the separation membrane, efficient CO2 fixation is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a carbon dioxide chemical chain cracking coupled catalytic disproportionation fixation method, belonging to the technical field of combustion chemical industry and materials. Background Art

[0002] Since the industrial age, the economy has developed rapidly, and human demand for energy has increased day by day. At present, the world's energy is mainly fossil fuels, mainly oil, coal, and natural gas. Due to the large-scale burning of fossil fuels, the content of carbon dioxide (CO2) in the atmosphere has increased sharply, leading to a serious global greenhouse effect, causing a series of serious problems such as rising global average temperature, melting glaciers, and rising sea levels, which have seriously affected human production and life. As we all know, CO2 is a natural, abundant, cheap and easily available carbon source. Therefore, converting greenhouse gas CO2 into C form through chemical chain coupled disproportionation reaction can not only reduce the content of CO2 in the atmosphere, but also obtain high value-added carbon material products, which is of great significance to human survival and ecological environment.

[0003] At present, our main energy consumption still relies on fossil fuels, so eliminating anthropogenic CO2 will be an attractive strategy. It is well known that in addition to carbon capture (CCS) technology, another method is to capture CO2 and convert it into other value-added chemicals. The carbon-oxygen bond in CO2 is very stable and inert, so it is particularly important to choose a suitable catalyst. The chemical chaining cracking technology uses lattice oxygen in perovskite catalysts to replace gaseous oxidants to participate in the reaction, and promotes the cracking process through oxygen vacancies during the reduction process. Compared with traditional cracking processes, the chemical chaining cracking of carbon dioxide using perovskite catalysts has the following potential advantages: 1) Oxygen carriers provide oxygen vacancies for the CO2 cracking process; 2) In addition to oxygen vacancies, the transition metal reduction state on the perovskite surface can also serve as an activation center for CO2 cracking; 3) Perovskite catalysts have a stable structure and can still maintain high catalytic performance after 50 cycles; 4) Use low-grade fuel gas to reduce the catalyst to achieve CO2 reuse.

[0004] The CO obtained by chemical chain cracking of CO2 is coupled with a catalytic disproportionation reaction to fix the C element in CO2. The product gas is separated by a mixed matrix membrane, and CO continues to undergo a disproportionation reaction, and CO2 is passed into the cracking reactor. The main gas components at the outlet of the disproportionation reactor are carbon monoxide, carbon dioxide and nitrogen. xFixed as C, separating carbon monoxide from the mixed gas is the key process. Traditional processes such as cryogenic distillation, absorption and adsorption can be used for CO separation, but the use of membranes has many advantages, such as easy manufacturing, environmental protection, low cost and high applicability. However, most of the current research on the use of membranes to separate CO focuses only on liquid membranes or carrier forms. From the perspective of processability and safety, solid membranes are more attractive than liquid membranes. They are easy to operate and there is no possibility of liquid leakage. However, due to the low diffusivity and solubility of CO, and its poorer permeability than other gases (such as CO2), the separation of CO gas by membranes is somewhat challenging. Summary of the invention

[0005] In view of the problems of insufficient catalyst stability and low carbon fixation efficiency in existing carbon dioxide fixation technologies, the present invention proposes a carbon dioxide chemical chain cracking coupled catalytic disproportionation fixation method, which aims to efficiently convert CO2 and reduce carbon dioxide emissions. In addition, it is also conducive to the realization of regenerative chemical chain cycle preparation.

[0006] The present invention is achieved by the following technical means:

[0007] The present invention first discloses a method for carbon dioxide chemical chain cracking coupled with catalytic disproportionation fixation, comprising the following steps:

[0008] Step 1): Catalytic cracking of CO2

[0009] The CO2 and the perovskite catalyst are subjected to a catalytic cracking reaction at a temperature of 650°C to 850°C;

[0010] In the carrier gas, the flow rate of carbon dioxide is greater than 0 and less than or equal to 20 mL / min. N2 is added to maintain the total flow rate at 30 mL / min and the total gas space velocity at 8000-24000 mL·g -1 ·h -1 .

[0011] Step 2): Regeneration of perovskite oxygen carrier

[0012] The perovskite catalyst after catalytic cracking reaction is introduced into blast furnace gas / low-grade fuel gas at a temperature of 650-850°C for reduction and regeneration, and CO2 and H2O are generated simultaneously;

[0013] The regenerated perovskite catalyst and the generated gas after drying are circulated to step 1).

[0014] Step 3): CO disproportionation reaction

[0015] The CO obtained in step 1) and the Fe / Al2O3 catalyst are subjected to a disproportionation reaction at a temperature of 300-500°C to obtain products CO2 and solid C.

[0016] Step 4): Gas separation

[0017] The CO obtained in step 3) and the CO2 that has not participated in the reaction are separated by a separation membrane, and the CO2 is circulated to step 1), and the CO is circulated to step 3).

[0018] This paper reports for the first time the use of perovskite catalysts as oxygen carriers for CO2 chemical chain cracking. The perovskite catalysts meet the high reduction capacity and CO2 cracking activity through the synergistic effect between the binary Ni and Fe centers. Under the same isothermal operating conditions, the long-term stability of La2NiFeO6 was further studied by 50 consecutive chemical chain cycles. The Ni element is desolvated from the perovskite through repeated redox reactions to form NiO x @LaFeO3 core-shell structure further increases oxygen storage capacity and reaction active sites. After the disproportionation reaction, CO / CO2 / N2 is separated by a mixed matrix membrane, further improving the carbon fixation rate of the overall reaction.

[0019] The technical solution of the present invention has a better carbon dioxide fixation effect and also has lower chemical chain regeneration conditions, thus having better industrial practical value.

[0020] The technical solution of the present invention, the application of perovskite-type catalytic oxygen carrier La2NiFeO6, through the synergistic catalytic effect of Ni and Fe and the regulation of oxygen vacancies is the key to the efficient and stable operation of the chemical chain CO2 cracking production period.

[0021] The technical solution of the present invention is to change the Fe loading in the Fe-based catalyst Fe / Al2O3 and find the best balance point between catalytic performance and stability, which is the key to the efficient and stable operation of the CO disproportionation reactor.

[0022] The technical solution of the present invention, the application of a mixed matrix membrane containing a polymer-silver salt-magnesium oxide nanosheet complex, is the key to improving the carbon fixation rate of the entire reaction process by separating the mixed gas CO2 / CO at the outlet of the disproportionation reactor and further cracking / disproportionating it.

[0023] In step 1) of the present invention, based on Fe 0 →Fe 3+ , Ni 0 →Ni 2+ The mechanism of CO2 cracking is realized. In the present invention, the perovskite catalyst can change the ratio of the B-site (Ni, Fe) elements.

[0024] In the present invention, step 1) is carried out in a fixed bed reactor.

[0025] Preferably, the flow rate of carbon dioxide in step 1) is 5 to 20 mL / min; more preferably, it is 10 to 15 mL / min.

[0026] Preferably, in step 1), the temperature of the CO2 cracking reaction is 700°C to 800°C.

[0027] Preferably, the CO yield in each cycle in step 1) is ≥1.5 mmol / g cat .

[0028] In the present invention, perovskite-type catalysts composed of other elements may also be used, such as other transition metal elements doped at the B position and different doping ratios to replace the perovskite.

[0029] In the present invention, in step 2), the gas composition of the blast furnace gas / low-grade fuel gas introduced includes: 28% to 33% CO by volume and 2% to 4% H2 by volume.

[0030] In the present invention, step 2) is carried out under a reducing atmosphere of blast furnace gas / low-grade fuel gas;

[0031] Preferably, the CO2 atmosphere comes from the gas produced in step 2).

[0032] In the present invention, in step 2), the regeneration temperature is 700°C to 800°C.

[0033] In the step 2), the regeneration reactor is powered by solar energy or industrial waste heat.

[0034] In the present invention, the step 2) is carried out in a fixed bed reactor.

[0035] In step 3) of the present invention, based on Fe 0 →Fe 3+ The mechanism of CO disproportionation is realized. In the present invention, the Fe-based catalyst can change the loading amount of Fe active metal and the type of carrier oxide such as Al2O3, MgO, SiO2, etc.

[0036] Preferably, in step 3), the disproportionation reaction temperature is 400-500°C.

[0037] Preferably, in step 3), the Fe loading is 3% to 8%.

[0038] In step 4) of the present invention, the mixed gas at the outlet of the disproportionation reactor is separated by using a mixed matrix membrane containing a polymer-silver salt-magnesium oxide nanosheet complex, and the composition of the complex can be further changed to optimize the permeability and selectivity of the separation membrane.

[0039] Preferably, in step 4), the mass ratio of phenyl methacrylate to methacrylic acid in the mixed matrix membrane is 8:2 to 6:4.

[0040] Preferably, the gas separated by the separation membrane is returned to the CO2 cracking reactor in step 1) and the CO disproportionation reactor in step 3) respectively.

[0041] The beneficial effects of the present invention are:

[0042] 1. This invention reports for the first time the use of La2NiFeO6, a perovskite-type catalytic oxygen carrier, to chemically catalyze the cracking of CO2. Compared with the existing CO2 cracking process, the catalyst has better cycle performance and helps to obtain better and higher CO yields. The CO yields of a single perovskite in five cycles are similar, and the average CO yields of LaNiO3 and LaFeO3 per cycle are 0.45 and 0.41 mmol / g, respectively. cat On the other hand, the average CO yield per cycle of double perovskite La2NiFeO6 is improved to 2.14mmol / g cat , which is more than 4.7 times that of other single perovskites.

[0043] 2. Based on the double perovskite La2NiFeO6 catalyzing the CO2 cracking reaction of the present invention, compared with the single perovskite LaNiO3 and LaFeO3, the CO yield of the double perovskite La2NiFeO6 remained almost unchanged throughout the cycle, while the CO yield of the double perovskite La2NiFeO6 gradually increased, and the CO yield at the 5th cycle was 2.32mmol / g cat , which is about 11% higher than the second cycle.

[0044] 3. Based on the treatment process of step 3) of the present invention, the catalytic effect of CO disproportionation reaction is further improved by changing the Fe loading amount. The CO conversion rate of 5wt% Fe / Al2O3 catalyst at 450°C reaches 45%.

[0045] 4. The mixed matrix membrane containing polymer-silver salt-magnesium oxide nanosheet complex based on step 4) of the present invention, wherein the mass ratio of methyl methacrylate phenyl ether to methacrylic acid is 7:3, has the highest CO permeability and CO2 blocking ability, wherein the CO permeability reaches 79GPU, and the separation performance reaches CO / N2=14.7, CO / CO2=12.

[0046] Based on the above analysis, it can be seen that the CO2 chemical chain cracking based on the double perovskite La2NiFeO6 catalytic oxygen carrier coupled with the Fe-based catalyst CO catalytic disproportionation is simple and easy to operate, with high chemical chain cracking catalyst regeneration stability, good separation membrane effect, and high carbon fixation rate. It is suitable for industrial applications and can achieve significant CO2 emission reduction effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The figure is a flow chart of the process of the present invention.

[0048] Figure 2 This is the XRD pattern of the catalytic oxygen carriers used for the catalytic cracking of different CO2 in Comparative Example 1.

[0049] Figure 3 This is a graph of the CO yield after 50 cycles of chemical looping CO2 cracking in Example 1.

[0050] Figure 4 This is a graph of CO conversion rates at different temperatures for catalysts with different Fe loadings (1, 3, 5 wt%) in the CO disproportionation reaction. DETAILED DESCRIPTION

[0051] The present invention is further described below in conjunction with the embodiments, comparative examples and accompanying drawings. Figure 1 shown.

[0052] Example 1

[0053] 1) 1.000g of perovskite-type catalytic oxygen carrier La2NiFeO6 was introduced into a CO2 cracking reactor, and the temperature was raised to 700°C at a heating rate of 50°C / min. N2 was used as a carrier gas with a flow rate of 15mL / min. After reaching the reaction temperature, CO2 was added to the carrier gas at a flow rate of 15mL / min, and the reaction time was 10min. The main products were CO and O2, containing a small amount of unreacted CO2.

[0054] 2) After the cracking is completed, the atmosphere is switched to 100 vol% N2 at a flow rate of 15 mL / min, and the purge is carried out for 10 minutes to enter the oxygen carrier regeneration stage. At a temperature of 700°C, blast furnace gas / low-grade fuel gas containing CO (28%) and H2 (2%) is introduced at a flow rate of 15 mL / min for 20 minutes. The product is a mixture of CO2 and H2O. At the same time, La2O3, NiO x , FeO x And LaFeO3 and others are reduced to La2NiFeO6 (desolventized NiFe alloy).

[0055] 3) 1.000g of 5wt% Fe / Al2O3 catalyst was introduced into the CO disproportionation reactor, and the temperature was raised to 450°C at a heating rate of 50°C / min, with N2 as the carrier gas at a flow rate of 15mL / min. After reaching the reaction temperature, CO produced by the cracking of CO2 was introduced into the disproportionation reactor at a controlled flow rate of 15mL / min. The main products were CO2 and C, including some CO that did not participate in the reaction.

[0056] 4) The tail gas after the disproportionation reaction is passed through a mixed matrix membrane composite separation membrane containing a polymer-silver salt-magnesium oxide nanosheet complex with a mass ratio of phenyl methacrylate to methacrylic acid of 7:3, and the permeated CO is re-introduced into the disproportionation reactor for catalytic disproportionation, and the CO2 is returned to the catalytic cracking reactor in step 1) for conversion.

[0057] The gas produced was continuously collected and analyzed at each cycle stage of the catalytic cracking reactor to determine the change trend of the yield of each gas component and the total gas yield over time. After 50 chemical chain cycles, the average CO yield of La2NiFeO6 at 700℃ was 2.14mmol / g cat The maximum CO generation rate is 1.69mmol / g cat / min(such as Figure 3 As shown). The gas produced was continuously collected and analyzed at the outlet of the CO disproportionation reactor, and the gas components and yields were determined. The CO conversion rate of the 5wt% Fe / Al2O3 catalyst at 450°C reached 45%. The performance of the separation membrane was analyzed, and the CO permeability and separation performance were tested. The CO permeability reached 79GPU, and the separation performance reached CO / N2=14.7, CO / CO2=12.

[0058] Example 2

[0059] Compared with Example 1, the only difference is that the reaction temperature is different during the cracking process.

[0060] 1) 1.000g of perovskite-type catalytic oxygen carrier La2NiFeO6 was introduced into a CO2 cracking reactor, and the temperature was raised to 750°C at a heating rate of 50°C / min. N2 was used as a carrier gas with a flow rate of 15mL / min. After reaching the reaction temperature, CO2 was added to the carrier gas at a flow rate of 15mL / min, and the reaction time was 10min. The main products were CO and O2, containing a small amount of unreacted CO2.

[0061] 2) After the cracking is completed, the atmosphere is switched to 100 vol.% N2 at a flow rate of 15 mL / min, and the purge is carried out for 10 minutes to enter the oxygen carrier regeneration stage. At a temperature of 700°C, blast furnace gas / low-grade fuel gas containing CO (28%) and H2 (2%) is introduced at a flow rate of 15 mL / min for 20 minutes. The product is a mixture of CO2 and H2O. At the same time, La2O3, NiO x , FeO x And LaFeO3 and others are reduced to La2NiFeO6 (desolventized NiFe alloy).

[0062] 3) 1.000g of 5wt% Fe / Al2O3 catalyst was introduced into the CO disproportionation reactor, and the temperature was raised to 450°C at a heating rate of 50°C / min, with N2 as the carrier gas at a flow rate of 15mL / min. After reaching the reaction temperature, CO produced by the cracking of CO2 was introduced into the disproportionation reactor at a controlled flow rate of 15mL / min. The main products were CO2 and C, including some CO that did not participate in the reaction.

[0063] 4) The tail gas after the disproportionation reaction is passed through a mixed matrix membrane composite separation membrane containing a polymer-silver salt-magnesium oxide nanosheet complex with a mass ratio of phenyl methacrylate to methacrylic acid of 7:3, and the permeated CO is re-introduced into the disproportionation reactor for catalytic disproportionation, and the CO2 is returned to the catalytic cracking reactor in step 1) for conversion.

[0064] The gas produced was continuously collected and analyzed at each cycle stage of the catalytic cracking reactor to determine the change trend of the yield of each gas component and the total gas yield over time. After 50 chemical chain cycles, the average CO yield of La2NiFeO6 at 750°C was 2.02mmol / g cat The maximum CO generation rate is 1.57mmol / g cat / min. The gas produced was continuously collected and analyzed at the outlet of the CO disproportionation reactor, and the gas components and yields were determined. The CO conversion rate of 5wt% Fe / Al2O3 catalyst reached 45% at 450°C. The performance of the separation membrane was analyzed, and the CO permeability and separation performance were tested. The CO permeability reached 79GPU, and the separation performance reached CO / N2=14.7, CO / CO2=12.

[0065] Example 3

[0066] Compared with Example 1, the only difference is that the gas atmosphere during the regeneration process is different.

[0067] 1) 1.000g of perovskite-type catalytic oxygen carrier La2NiFeO6 was introduced into a CO2 cracking reactor, and the temperature was raised to 700°C at a heating rate of 50°C / min. N2 was used as a carrier gas with a flow rate of 15mL / min. After reaching the reaction temperature, CO2 was added to the carrier gas at a flow rate of 15mL / min, and the reaction time was 10min. The main products were CO and O2, containing a small amount of unreacted CO2.

[0068] 2) After the cracking is completed, the atmosphere is switched to 100 vol.% N2 at a flow rate of 15 mL / min, and the purge is carried out for 10 minutes to enter the oxygen carrier regeneration stage. At a temperature of 700°C, blast furnace gas / low-grade fuel gas containing CO (33%) and H2 (4%) is introduced at a flow rate of 15 mL / min for 20 minutes. The product is a mixture of CO2 and H2O. At the same time, La2O3, NiO x, FeO x And LaFeO3 and others are reduced to La2NiFeO6 (desolventized NiFe alloy).

[0069] 3) 1.000g of 5wt% Fe / Al2O3 catalyst was introduced into the CO disproportionation reactor, and the temperature was raised to 450°C at a heating rate of 50°C / min, with N2 as the carrier gas at a flow rate of 15mL / min. After reaching the reaction temperature, CO produced by the cracking of CO2 was introduced into the disproportionation reactor at a controlled flow rate of 15mL / min. The main products were CO2 and C, including some CO that did not participate in the reaction.

[0070] 4) The tail gas after the disproportionation reaction is passed through a mixed matrix membrane composite separation membrane containing a polymer-silver salt-magnesium oxide nanosheet complex with a mass ratio of phenyl methacrylate to methacrylic acid of 7:3, and the permeated CO is re-introduced into the disproportionation reactor for catalytic disproportionation, and the CO2 is returned to the catalytic cracking reactor in step 1) for conversion.

[0071] The gas produced was continuously collected and analyzed at each cycle stage of the catalytic cracking reactor to determine the change trend of the yield of each gas component and the total gas yield over time. After 50 chemical chain cycles, the average CO yield of La2NiFeO6 at 700℃ was 2.14mmol / g cat The maximum CO generation rate is 1.69mmol / g cat / min. The gas produced was continuously collected and analyzed at the outlet of the CO disproportionation reactor, and the gas components and yields were determined. The CO conversion rate of 5wt% Fe / Al2O3 catalyst reached 45% at 450°C. The performance of the separation membrane was analyzed, and the CO permeability and separation performance were tested. The CO permeability reached 79GPU, and the separation performance reached CO / N2=14.7, CO / CO2=12.

[0072] Example 4

[0073] Compared with Example 1, the only difference is that the Fe loading of the catalyst for the disproportionation reaction is different, such as Figure 4 As shown, with the increase of Fe loading (1%-3%-5%), the CO conversion rate at the same temperature gradually increases. The 5% Fe / Al2O3 catalyst has the best CO disproportionation performance, and the CO conversion rate reaches 45%.

[0074] 1) 1.000g of perovskite-type catalytic oxygen carrier La2NiFeO6 was introduced into a CO2 cracking reactor, and the temperature was raised to 700°C at a heating rate of 50°C / min. N2 was used as a carrier gas with a flow rate of 15mL / min. After reaching the reaction temperature, CO2 was added to the carrier gas at a flow rate of 15mL / min, and the reaction time was 10min. The main products were CO and O2, containing a small amount of unreacted CO2.

[0075] 2) After the cracking is completed, the atmosphere is switched to 100 vol.% N2 at a flow rate of 15 mL / min, and the purge is carried out for 10 minutes to enter the oxygen carrier regeneration stage. At a temperature of 700°C, blast furnace gas / low-grade fuel gas containing CO (28%) and H2 (2%) is introduced at a flow rate of 15 mL / min for 20 minutes. The product is a mixture of CO2 and H2O. At the same time, La2O3, NiO x , FeO x And LaFeO3 and others are reduced to La2NiFeO6 (desolventized NiFe alloy).

[0076] 3) 1.000g of 3wt% Fe / Al2O3 catalyst was introduced into the CO disproportionation reactor, and the temperature was raised to 450°C at a heating rate of 50°C / min, with N2 as the carrier gas at a flow rate of 15mL / min. After reaching the reaction temperature, CO produced by the cracking of CO2 was introduced into the disproportionation reactor at a controlled flow rate of 15mL / min. The main products were CO2 and C, including some CO that did not participate in the reaction.

[0077] 4) The tail gas after the disproportionation reaction is passed through a mixed matrix membrane composite separation membrane containing a polymer-silver salt-magnesium oxide nanosheet complex with a mass ratio of phenyl methacrylate to methacrylic acid of 7:3, and the permeated CO is re-introduced into the disproportionation reactor for catalytic disproportionation, and the CO2 is returned to the catalytic cracking reactor in step 1) for conversion.

[0078] The gas produced was continuously collected and analyzed at each cycle stage of the catalytic cracking reactor to determine the change trend of the yield of each gas component and the total gas yield over time. After 50 chemical chain cycles, the average CO yield of La2NiFeO6 at 750°C was 2.14mmol / g cat The maximum CO generation rate is 1.69mmol / g cat / min. The gas produced was continuously collected and analyzed at the outlet of the CO disproportionation reactor, and the gas components and yields were determined. The CO conversion rate of 3wt% Fe / Al2O3 catalyst at 450°C reached 27%. The performance of the separation membrane was analyzed, and the CO permeability and separation performance were tested. The CO permeability reached 79GPU, and the separation performance reached CO / N2=14.7, CO / CO2=12.

[0079] Example 5

[0080] Compared with Example 1, the only difference is that the composition of the separation membrane is different.

[0081] 1) 1.000g of perovskite-type catalytic oxygen carrier La2NiFeO6 was introduced into a CO2 cracking reactor, and the temperature was raised to 700°C at a heating rate of 50°C / min. N2 was used as a carrier gas with a flow rate of 15mL / min. After reaching the reaction temperature, CO2 was added to the carrier gas at a flow rate of 15mL / min, and the reaction time was 10min. The main products were CO and O2, containing a small amount of unreacted CO2.

[0082] 2) After the cracking is completed, the atmosphere is switched to 100 vol.% N2 at a flow rate of 15 mL / min, and the purge is carried out for 10 minutes to enter the oxygen carrier regeneration stage. At a temperature of 700°C, blast furnace gas / low-grade fuel gas containing CO (28%) and H2 (2%) is introduced at a flow rate of 15 mL / min for 20 minutes. The product is a mixture of CO2 and H2O. At the same time, La2O3, NiO x , FeO x And LaFeO3 and others are reduced to La2NiFeO6 (desolventized NiFe alloy).

[0083] 3) 1.000g of 5wt% Fe / Al2O3 catalyst was introduced into the CO disproportionation reactor, and the temperature was raised to 450°C at a heating rate of 50°C / min, with N2 as the carrier gas at a flow rate of 15mL / min. After reaching the reaction temperature, CO produced by the cracking of CO2 was introduced into the disproportionation reactor at a controlled flow rate of 15mL / min. The main products were CO2 and C, including some CO that did not participate in the reaction.

[0084] 4) The tail gas after the disproportionation reaction is passed through a mixed matrix membrane composite separation membrane containing a polymer-silver salt-magnesium oxide nanosheet complex with a mass ratio of phenyl methacrylate to methacrylic acid of 8:2, and the permeated CO is re-introduced into the disproportionation reactor for catalytic disproportionation, and the CO2 is returned to the catalytic cracking reactor in step 1) for conversion.

[0085] The gas produced was continuously collected and analyzed at each cycle stage of the catalytic cracking reactor to determine the change trend of the yield of each gas component and the total gas yield over time. After 50 chemical chain cycles, the average CO yield of La2NiFeO6 at 700℃ was 2.14mmol / g cat The maximum CO generation rate is 1.69mmol / g cat / min. The gas produced was continuously collected and analyzed at the outlet of the CO disproportionation reactor, and the gas components and yields were determined. The CO conversion rate of 5wt% Fe / Al2O3 catalyst reached 45% at 450°C. The performance of the separation membrane was analyzed, and the CO permeability and separation performance were tested. The CO permeability was 45GPU, and the separation performance reached CO / N2=2.3 and CO / CO2=2.1.

[0086] Comparative Example 1

[0087] Compared with Example 1, the only difference is that LaNiO3 or LaFeO3 is added during the CO2 cracking process.

[0088] 1) 1.000g of perovskite-type catalytic oxygen carrier LaNiO3 or LaFeO3 was introduced into the CO2 cracking reactor (XRD phase analysis showed that Figure 2 As shown, it shows that a single-phase perovskite catalyst is prepared), the temperature is raised to 700°C at a heating rate of 50°C / min, N2 is used as a carrier gas, and its flow rate is 15mL / min. After reaching the reaction temperature, CO2 is added to the carrier gas, and the CO2 flow rate is 15mL / min. The reaction time is 10min. The main products are CO and O2, containing a small amount of unreacted CO2.

[0089] 2) After the cracking is completed, the atmosphere is switched to 100 vol.% N2 at a flow rate of 15 mL / min, and the purge is carried out for 10 minutes to enter the oxygen carrier regeneration stage. At a temperature of 700°C, blast furnace gas / low-grade fuel gas containing CO (28%) and H2 (2%) is introduced at a flow rate of 15 mL / min for 20 minutes. The product is a mixture of CO2 and H2O. At the same time, La2O3, NiO x , FeO x And LaFeO3 and others are reduced to La2NiFeO6 (desolventized NiFe alloy).

[0090] 3) 1.000g of 5wt% Fe / Al2O3 catalyst was introduced into the CO disproportionation reactor, and the temperature was raised to 450°C at a heating rate of 50°C / min, with N2 as the carrier gas at a flow rate of 15mL / min. After reaching the reaction temperature, CO produced by the cracking of CO2 was introduced into the disproportionation reactor at a controlled flow rate of 15mL / min. The main products were CO2 and C, including some CO that did not participate in the reaction.

[0091] 4) The tail gas after the disproportionation reaction is passed through a mixed matrix membrane composite separation membrane containing a polymer-silver salt-magnesium oxide nanosheet complex with a mass ratio of phenyl methacrylate to methacrylic acid of 7:3, and the permeated CO is re-introduced into the disproportionation reactor for catalytic disproportionation, and the CO2 is returned to the catalytic cracking reactor in step 1) for conversion.

[0092] The gas produced was continuously collected and analyzed at each cycle stage of the catalytic cracking reactor to determine the change trend of the yield of each gas component and the total gas yield over time. After 50 chemical chain cycles, the average CO yield of LaNiO3 at 700°C was 0.45mmol / g cat , LaFeO3 is 0.41mmol / g catThe gas produced was continuously collected and analyzed at the outlet of the CO disproportionation reactor, and the gas components and yields were determined. The CO conversion rate of 5wt% Fe / Al2O3 catalyst reached 45% at 450°C. The performance of the separation membrane was analyzed, and the CO permeability and separation performance were tested. The CO permeability reached 79GPU, and the separation performance reached CO / N2=14.7, CO / CO2=12.

[0093] Comparative Example 2

[0094] Compared with Example 1, the only difference is that the CO2 cracking catalyst uses Mn 0.2 Co 0.8 Fe2O4.

[0095] 1) 1.000g of dual elements Mn and Co are doped into ferrite Mn 0.2 Co 0.8 Fe2O4 was introduced into the CO2 cracking reactor and heated to 700℃ at a heating rate of 50℃ / min. N2 was used as the carrier gas with a flow rate of 15mL / min. After reaching the reaction temperature, CO2 was added to the carrier gas at a flow rate of 15mL / min. The reaction time was 10min. The main products were CO and O2, with a small amount of unreacted CO2.

[0096] 2) After the cracking is completed, the atmosphere is switched to 100 vol.% N2 at a flow rate of 15 mL / min, and the purge is carried out for 10 minutes to enter the oxygen carrier regeneration stage. At a temperature of 700°C, blast furnace gas / low-grade fuel gas containing CO (28%) and H2 (2%) is introduced at a flow rate of 15 mL / min for 20 minutes. The product is a mixture of CO2 and H2O. At the same time, La2O3, NiO x , FeO x And LaFeO3 and others are reduced to La2NiFeO6 (desolventized NiFe alloy).

[0097] 3) 1.000g of 5wt% Fe / Al2O3 catalyst was introduced into the CO disproportionation reactor, and the temperature was raised to 450°C at a heating rate of 50°C / min, with N2 as the carrier gas at a flow rate of 15mL / min. After reaching the reaction temperature, CO produced by the cracking of CO2 was introduced into the disproportionation reactor at a controlled flow rate of 15mL / min. The main products were CO2 and C, including some CO that did not participate in the reaction.

[0098] 4) The tail gas after the disproportionation reaction is passed through a mixed matrix membrane composite separation membrane containing a polymer-silver salt-magnesium oxide nanosheet complex with a mass ratio of phenyl methacrylate to methacrylic acid of 7:3, and the permeated CO is re-introduced into the disproportionation reactor for catalytic disproportionation, and the CO2 is returned to the catalytic cracking reactor in step 1) for conversion.

[0099] The gas produced was continuously collected and analyzed at each cycle stage of the catalytic cracking reactor to determine the change trend of the yield of each gas component and the total gas yield over time. 0.2 Co 0.8 The average CO yield of Fe2O4 at 700℃ is 0.96mmol / g cat The gas produced was continuously collected and analyzed at the outlet of the CO disproportionation reactor, and the gas components and yields were determined. The CO conversion rate of 5wt% Fe / Al2O3 catalyst reached 45% at 450°C. The performance of the separation membrane was analyzed, and the CO permeability and separation performance were tested. The CO permeability reached 79GPU, and the separation performance reached CO / N2=14.7, CO / CO2=12.

[0100] Comparative Example 3

[0101] Compared with Example 1, the only difference is that no silver salt and magnesium oxide nanosheets are added to the composite matrix separation membrane.

[0102] 1) 1.000g of perovskite-type catalytic oxygen carrier La2NiFeO6 was introduced into a CO2 cracking reactor, and the temperature was raised to 700°C at a heating rate of 50°C / min. N2 was used as a carrier gas with a flow rate of 15mL / min. After reaching the reaction temperature, CO2 was added to the carrier gas at a flow rate of 15mL / min, and the reaction time was 10min. The main products were CO and O2, containing a small amount of unreacted CO2.

[0103] 2) After the cracking is completed, the atmosphere is switched to 100 vol.% N2 at a flow rate of 15 mL / min, and the purge is carried out for 10 minutes to enter the oxygen carrier regeneration stage. At a temperature of 700°C, blast furnace gas / low-grade fuel gas containing CO (28%) and H2 (2%) is introduced at a flow rate of 15 mL / min for 20 minutes. The product is a mixture of CO2 and H2O. At the same time, La2O3, NiO x , FeO x And LaFeO3 and others are reduced to La2NiFeO6 (desolventized NiFe alloy).

[0104] 3) 1.000g of 5wt% Fe / Al2O3 catalyst was introduced into the CO disproportionation reactor, and the temperature was raised to 450°C at a heating rate of 50°C / min, with N2 as the carrier gas at a flow rate of 15mL / min. After reaching the reaction temperature, CO produced by the cracking of CO2 was introduced into the disproportionation reactor at a controlled flow rate of 15mL / min. The main products were CO2 and C, including some CO that did not participate in the reaction.

[0105] 4) The tail gas after the disproportionation reaction is passed through a mixed matrix membrane composite separation membrane having a mass ratio of phenyl methacrylate to methacrylic acid of 7:3, and the permeated CO is re-introduced into the disproportionation reactor for catalytic disproportionation, and the CO2 is returned to the catalytic cracking reactor in step 1) for conversion.

[0106] The gas produced was continuously collected and analyzed at each cycle stage of the catalytic cracking reactor to determine the change trend of the yield of each gas component and the total gas yield over time. After 50 chemical chain cycles, the average CO yield of La2NiFeO6 at 700℃ was 2.14mmol / g cat The maximum CO generation rate is 1.69mmol / g cat / min. The gas produced was continuously collected and analyzed at the outlet of the CO disproportionation reactor, and the gas components and yields were determined. The CO conversion rate of 5wt% Fe / Al2O3 catalyst reached 45% at 450°C. The performance of the separation membrane was analyzed, and the CO permeability and separation performance were tested. The CO permeability was 4.7GPU, and the separation performance was CO / N2=0.7, CO / CO2=0.6.

[0107] The present invention proposes a method for carbon dioxide chemical chain cracking coupled with catalytic disproportionation fixation, using double perovskite La2NiFeO6 as a catalyst, in the CO2 cracking reactor part, under the action of a perovskite-type catalytic oxygen carrier, CO2 is cracked to generate gaseous products such as CO and O2, and La2O3, NiO x , FeO x and LaFeO3 and other substances, enter the regeneration reactor together; in the regeneration reactor part, under the action of blast furnace gas / low-grade fuel gas, it is reduced to La2NiFeO6 (NiFe alloy desolvation) and returns to the CO2 cracking reactor again. The continuous conversion forms a chemical chain process. Compared with the existing biomass chemical chain gasification technology, the creativity is mainly reflected in:

[0108] 1) In the process of CO2 chemical chain catalytic cracking, the catalytic La2NiFeO6 system and the oxygen carrier effect realize an efficient and stable chemical chain CO2 cracking process, which improves the CO yield. The average CO yield at 700℃ is 2.14mmol / g cat The maximum CO generation rate is 1.69mmol / g cat / min, which are 4.7 times and more than 10 times that of simple ABO3-type perovskite, respectively;

[0109] 2) The catalytic oxygen carrier is reduced by blast furnace gas / low-grade fuel gas, making full use of industrial waste gas to achieve the purpose of energy conservation and emission reduction;

[0110] 3) By adjusting the active metal Fe loading, disproportionation reaction temperature and other variables, the CO conversion rate is maximized to increase the carbon fixation rate of the overall process. A conversion rate of 45% was achieved at 450°C through the catalytic effect of 5wt% Fe / Al2O3.

[0111] 4) The best separation performance was obtained by regulating the matrix composition and ratio of the composite matrix membrane. When the mass ratio of phenyl methacrylate to methacrylic acid was 7:3, the mixed matrix membrane containing polymer-silver salt-magnesium oxide nanosheets complex had the best CO permeability and separation performance, with the CO permeability reaching 79GPU, and the separation performance reaching CO / N2=14.7 and CO / CO2=12.

[0112] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of equivalent transformations, and these equivalent transformations all belong to the protection scope of the present invention. It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further explain various possible combinations. In addition, the various different embodiments of the present invention can also be arbitrarily combined, as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for carbon dioxide chemical chain cracking coupled with catalytic disproportionation fixation, comprising the following steps: Step 1): Catalytic cracking of CO2 The CO2 and the perovskite catalyst are subjected to high-temperature catalytic cracking in a fixed bed reactor; Step 2): Regeneration of perovskite oxygen carrier The perovskite catalyst after the catalytic cracking reaction is introduced into blast furnace gas / low-grade fuel gas at high temperature for reduction regeneration, and CO2 and H2O are generated simultaneously, and the regenerated perovskite catalyst and the generated gas after drying are circulated to step 1); Step 3): CO disproportionation reaction The CO obtained in step 1) and the Fe / Al2O3 catalyst are subjected to a disproportionation reaction at a high temperature to obtain CO2 and solid C; Step 4): Gas separation The gases CO, CO2 and N2 in step 3) are separated by a separation membrane, the separated CO2 is circulated to step 1) to participate in the CO2 cracking reaction, and the separated CO is circulated to step 3) to participate in the CO disproportionation reaction.

2. A method for fixing carbon dioxide by chemical chaining pyrolysis coupled with catalytic disproportionation according to claim 1, wherein: Step 1) The high temperature is: 650°C to 850°C; The gas conditions of the catalytic cracking reaction are: 0<CO2 flow rate ≤ 20mL / min, supplement N2 to maintain the total flow rate at 30mL / min, and maintain the total gas space velocity at 8000~24000mL·g -1 ·h -1 .

3. A method for fixing carbon dioxide by chemical chain pyrolysis coupled with catalytic disproportionation according to claim 2, wherein: The CO2 flow rate is 5-20 mL / min.

4. A method for fixing carbon dioxide by chemical chaining pyrolysis coupled with catalytic disproportionation according to claim 3, wherein: The CO2 flow rate is 10-15 mL / min.

5. A method for fixing carbon dioxide by chemical chain pyrolysis coupled with catalytic disproportionation according to claim 1, wherein: The gas components of the blast furnace gas / low-grade fuel gas introduced in step 2) include: 28% to 33% CO by volume and 2% to 4% H2 by volume.

6. A method for fixing carbon dioxide by chemical chaining pyrolysis coupled with catalytic disproportionation according to claim 1, wherein: The high temperature in step 2) is 650-850°C.

7. A method for fixing carbon dioxide by chemical chain pyrolysis coupled with catalytic disproportionation according to claim 1, wherein: Step 3) the Fe loading in the Fe / Al2O3 catalyst is 1% to 10%; The high temperature is 300-500°C.

8. A method for fixing carbon dioxide by chemical chaining pyrolysis coupled with catalytic disproportionation according to claim 1, wherein: Step 4) The separation membrane is a mixed matrix membrane containing a polymer-silver salt-magnesium oxide nanosheet complex.

9. A method for fixing carbon dioxide by chemical chaining pyrolysis coupled with catalytic disproportionation according to claim 8, wherein: The mass ratio of phenyl methacrylate to methacrylic acid in the mixed matrix membrane is 9:1 to 5:

5.

10. A method for fixing carbon dioxide by chemical chaining pyrolysis coupled with catalytic disproportionation according to claim 1, wherein: Step 1) CO yield in each cycle ≥ 1.5 mmol / g cat ; The CO2 obtained in step 3) and step 4) enters a CO2 storage tank with a control system to control the flow of the gas returning to step 1) to participate in the CO2 cracking reaction.